Bunch microclimate influence amino acids and phenolic profiles of Pinot noir grape berries - Moukarzel, Romy; Parker, Amber K.; Schelezki, Olaf J.; Gregan, Scott M.; Jordan, Brian (Frontiers in Plant Science, 2023)
The increase of temperature due to climate change at different phenological stages of grapevine has already been demonstrated to affect accumulation of primary and secondary metabolites in grape berries. This has a significant implication for Pinot noir especially in New Zealand context as these compounds can have direct and indirect effects on wine quality. Therefore, this study investigates how varying bunch microclimate through changes in temperature applied at veraison stage can affect: fresh weight, total soluble solids, the accumulation of anthocyanins, total phenolics and amino acids of the grape berries. This was studied over two growing seasons (2018/19 and 2019/20) with Pinot noir vines being grown at two different temperatures in controlled environment (CE) chambers. The vines were exposed to 800 µmol/m2/s irradiance with diurnal changes in day (22°C or 30°C) and night (15°C) temperatures. This experimental set up enabled us to determine the accumulation of these metabolite at harvest (both seasons) and throughout berry development (second season). The results showed that berry weight was not influenced by temperature increase. The total soluble solids (TSS) were significantly increased at 30°C, however, this was not at the expense of berry weight (i.e., water loss). Anthocyanin content was reduced at higher temperature in the first season but there was no change in phenolic content in response to temperature treatments in either season. The concentrations of total amino acids at harvest increased in response to the higher temperature in the second season only. In addition, in the time course analysis of the second season, the accumulation of amino acids was increased at mid-ripening and ripening stage with the increased temperature. Significant qualitative changes in amino acid composition specifically the α-ketoglutarate family (i.e., glutamine, arginine, and proline) were found between the two temperatures. This study is the first to provide detailed analysis and quantification of individual amino acids and phenolics in Pinot noir in response to changes in temperature applied at veraison which could aid to develop adaptation strategies for viticulture in the future.